The complete business process handbook : body of knowledge from process modeling to bpm. - Rosing, Mark von; Scheel, Henrik von; Scheer, August-Wilhelm (Elsevier, 2014)
The Complete Business Process Handbook is the most comprehensive body of knowledge on business processes. With expert guidance from authors and editors Mark von Rosing and Henrik von Scheel, it is written as a practical guide for Executives, Practitioners, Managers and Students by the authorities that have shaped the way we think and work with process today. This book provides everything you need to know about the processes and frameworks, methods, and approaches to implement BPM. Through real-world examples, best practices, LEADing practices and advice from experts, readers will understan.